Molecular Detection of T. Gondii DNA by Polymerase Chain Reaction in Blood Samples of Pregnant Women Attending Tertiary Care Unit in Islamabad, Pakistan - Naila Rafique, Nida Basharat Khan, Nosheen Nabi, Sidra Nosheen Kiani, Sidra Sheikh, Sabah Kaleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Purpose: Toxoplasmosis is caused by Toxoplasma gondii and is mainly diagnosed through serological methods, but the sensitivity is insufficient. When it fails, one must rely on direct detection of parasites or DNA testing via polymerase chain reaction (PCR). Our goal is to establish a molecular tool for domestic toxoplasmosis research through PCR technology targeting the B1 gene and compare it with ELISA results. Design and Setting: This study was conducted at the Rawal Institute of Health Sciences, Islamabad between May 2023 and July 2023 on pregnant women attending Rawal General Hospital, Islamabad. Patients and Methods: Peripheral blood samples were collected from patients (n=137). DNA was extracted and the B1 Toxoplasma gondii gene was amplified by PCR. Amplicons were visualized and sequenced, and the results analyzed. For comparison, anti-T. gondii IgG and IgM in serum were measured by enzyme-linked immunosorbent assay (ELISA). Results: Among the 137 samples tested, 56 (41%) had B1 gene amplification detected by PCR. DNA sequencing confirmed these results. The IgM-ELISA test detected 9 of these cases (6.5%). Immunoglobulin G test results were positive in 53 patients (38.6%). Conclusion: This study demonstrates the need for PCR as a confirmatory test in addition to serological testing to detect recent infection. We recommend nationwide implementation of these molecular diagnostic tools. Keywords: T. Gondii DNA, Polymerase Chain Reaction, Pregnant Women, PCR.